F Transparansi dan Akuntabilitas: Pilar Tata Kelola dalam Keuangan Islam. - Nursupa’ah Nursupa’ah; Muhamad Yusup; Hj. Siti Nurul Kaherani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Robust governance constitutes a crucial foundation for the sustainability and competitiveness of the Islamic financial industry. This study aims to analyze the role of transparency and accountability as two main pillars of Islamic financial governance, focusing on their implementation, effectiveness, and impact. The discussion is centered on three key research questions: (1) the implementation and challenges of transparency and accountability in profit-sharing products (mudharabah and musyarakah), (2) the effectiveness of the Sharia Supervisory Board (SSB) in ensuring sharia accountability and transparency and its influence on public trust, and (3) the significant impact of disclosure transparency and accountability levels on financial performance and institutional stability. The literature review indicates that although the implementation of transparency and accountability in profit-sharing products faces challenges such as information asymmetry and accounting complexity, the effectiveness of the SSB—supported by independence and competence—has proven to be a catalyst for enhancing public trust. Furthermore, commitment to transparency and accountability is not merely a fulfillment of sharia principles but is also positively correlated with improved financial performance (such as profitability) and institutional stability through mechanisms that reduce the cost of capital and enhance resilience to crises. The study concludes that strengthening these two pillars represents a sustainable business strategy. Accordingly, recommendations are proposed for Islamic financial institutions, regulatory authorities, Sharia Supervisory Boards, and the public to synergistically promote more transparent and accountable governance practices in order to realize an Islamic financial system that is not only profitable but also resilient and trusted.